Cost-effectiveness of percutaneous coronary intervention versus bypass surgery from a Dutch perspective. Issue 24 (9th November 2015) - Osnabrugge, Ruben L; Magnuson, Elizabeth A; Serruys, Patrick W; Campos, Carlos M; Wang, Kaijun; van Klaveren, David; Farooq, Vasim; Abdallah, Mouin S; Li, Haiyan; Vilain, Katherine A; Steyerberg, Ewout W; Morice, Marie-Claude; et al.
Abstract : Aims: Recent cost-effectiveness analyses of percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG) have been limited by a short time horizon or were restricted to the US healthcare perspective. We, therefore, used individual patient-level data from the SYNTAX trial to evaluate the cost-effectiveness of PCI versus CABG from a European (Dutch) perspective. Methods and results: Between 2005 and 2007, 1800 patients with three-vessel or left main coronary artery disease were randomised to either CABG (n=897) or PCI with drug-eluting stents (DES; n=903). Costs were estimated for all patients based on observed healthcare resource usage over 5 years of follow-up. Health state utilities were evaluated with the EuroQOL questionnaire. A patient-level microsimulation model based on Dutch life-tables was used to extrapolate the 5-year in-trial data to a lifetime horizon. Although initial procedural costs were lower for CABG, total initial hospitalisation costs per patient were higher (€17 506 vs €14 037, p<0.001). PCI was more costly during the next 5 years of follow-up, due to more frequent hospitalisations, repeat revascularisation procedures and higher medication costs. Nevertheless, total 5-year costs remained €2465/patient higher with CABG. When the in-trial results were extrapolated to a lifetime horizon, CABG was projected to be economically attractive relative to DES-PCI, with gains in both life expectancy and quality-adjusted life expectancy. The incremental cost-effectiveness ratio (ICER) (€5390/quality-adjusted life year (QALY) gained) was favourable and remained <€80 000/QALY in >90% of the bootstrap replicates. Outcomes were similar when incorporating the prognostic impact of non-fatal myocardial infarction and stroke, as well as across a broad range of assumptions regarding the effect of CABG on post-trial survival and costs. However, DES-PCI was economically dominant compared with CABG in patients with a SYNTAX Score ≤22 or in those with left main disease. In patients for whom the SYNTAX Score II favoured PCI based on lower predicted 4-year mortality, PCI was also economically dominant, whereas in those patients for whom the SYNTAX Score II favoured surgery, CABG was highly economically attractive (ICER range, €2967 to €3737/QALY gained). Conclusions: For the broad population with three-vessel or left main disease who are candidates for either CABG or PCI, we found that CABG is a clinically and economically attractive revascularisation strategy compared with DES-PCI from a Dutch healthcare perspective. The cost-effectiveness of CABG versus PCI differed according to several anatomic factors, however. The newly developed SYNTAX Score II provides enhanced prognostic discrimination in this population, and may be a useful tool to guide resource allocation as well. Trial registration number: Clinical trial unique identifier: NCT00114972 (http://www.clinical-trials.gov )